Growth performance, carcass yield and gait score of Marshal broiler chicken reared on intensive and semi intensive management systems - Oluwadiya, B. O.; Adeyemi, O.A.; Sogunle, O.M.; Obasa O.A.; Ladokun, A.O. (Malaysian Journal of Animal Science, 2017)
The rearing system used in highly productive farms is often subjected to harsh criticism, one of the reasons being its failure to provide adequate welfare. A number of attempts have been made to introduce new technologies in rearing poultry for meat production aiming at improving rearing conditions, protecting the environment and enhancing the quality of poultry products. Given the above, one hundred and sixty eight unsexed 14-day old Marshall broiler chicks were used in a completely randomized design study to compare the effect of management systems (intensive and semi intensive) on the growth performance, carcass characteristics and gait score of broiler chickens. The experiment lasted for 42 d. Data were collected on weight gain, feed intake, feed conversion ratio, carcass yield and gait score. Result showed that birds on the intensive management system recorded higher weight gain (P < 0.05; 1.83 vs 1.37 kg) while feed conversion ratio was significantly higher in birds on the semi intensive management system (P < 0.05; 2.32 vs 2.15). Dressing and thigh weight percentages were higher in birds on the intensive management system (P > 0.05; 66.94%, 11.44%) than those in semi-intensive system (54.55%, 10.92%, respectively). For the gait score broiler birds on semi intensive management system recorded reduced number of cases of severe and slight leg problems (P < 0.05, 25.76% vs 49.3%). It was concluded that broiler birds should be reared on intensive management system for better growth performance and carcass yield. However, birds reared on semi intensive management system had fewer leg problems compared to birds reared on intensive management system. The fewer severe leg problems observed in birds on semi intensive management system will help improve their market value thereby making birds more profitable to rear on semi intensive management system.